Reduced renal function may explain the higher prevalence of hyperuricemia in older people - Wang, Yutang; Zhang, Wanlin; Qian, Tingting; Sun, Hui; Xu, Qun; Hou, Xujuan; Hu, Wenqi; Zhang, Guang; Drummond, Grant R.; Sobey, Christopher G.; Charchar, Fadi J.; Golledge, Jonathan; et al. (Scientific reports, 2021)
This study aimed to investigate the contribution of renal dysfunction to enhanced hyperuricemia prevalence in older people. A cohort of 13,288 Chinese people aged between 40 and 95 years were recruited from January to May 2019. Serum uric acid concentration and estimated glomerular filtration rate [eGFR] were measured. The associations between age or eGFR and serum uric acid or hyperuricemia were analyzed using linear or binary logistic regression adjusting for risk factors. Uric acid concentration and prevalence of hyperuricemia were greater in older participants. Adjustment for reduced renal function (eGFR < 60 mL/min/1.73 m 2 ) eliminated the associations between older age and higher uric acid concentration and between older age and higher prevalence of hyperuricemia diagnosis, whereas adjustment for other risk factors did not change those associations. Lower eGFR was associated with higher uric acid concentration both before (β = − 0.296, P < 0.001) and after adjustment for age (β = − 0.313, P < 0.001). Reduced renal function was associated with hyperuricemia diagnosis both before (odds ratio, OR, 3.64; 95% CI 3.10–4.28; P < 0.001) and after adjustment for age (adjusted OR, 3.82; 95% CI 3.22–4.54; P < 0.001). Mean serum uric acid and prevalence of hyperuricemia were higher in people with eGFR < 60 mL/min/1.73 m 2 than those with eGFR ≥ 60 mL/min/1.73 m 2 . The prevalence of reduced renal function increased with older age ( P < 0.001). This study suggests that reduced renal function can explain the increased uric acid levels and hyperuricemia diagnoses in older people.